(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Today’s greatest global challenges include managing the environmental crisis and promoting sustainable development. Within architecture, the measures and approaches taken to address these challenges vary. The environmental crisis has led to sustainability being considered primarily a global and ecological issue. However, academic debates suggest that sustainable architecture and issues of technological change should reconnect with the social and cultural contexts where development occurs (Guy, 2005). Using a case study, this paper examines the extent to which one specific architectural approach to sustainability interacts with particular local conditions.